Excretion and Residual Concentration Correlations of Salbutamol Between Edible Tissues and Living Samples in Pigs and Goats - Sun, Lei; Zhu, Minjuan; Shi, Jingfei; Mi, Kun; Ma, Wenjing; Xu, Xiangyue; Wang, Hanyu; Pan, Yuanhu; Tao, Yanfei; Liu, Zhenli; Huang, Lingli (Frontiers in Pharmacology, 2021)
Salbutamol (SAL) has been banned worldwide as a feed additive due to its damage to human health. However, benefit-driven illegal use still exists. This study observed the excretion and depletion of SAL in pigs and goats and investigated the concentration correlations between edible tissues and living samples to find a suitable living sample for pre-slaughter monitoring. After a single oral dosage of 1.2 mg/kg SAL, approximately 70% of the dose was excreted by pigs and goats. When supplied feed containing SAL (20 mg/kg) for 14 consecutive days, high concentrations of SAL were observed in liver and kidney of pigs and goats, and the longest persistence was observed in hair. Unlike pigs, SAL was presented primarily as conjugated SAL in goats. Urine could predict accurately SAL concentrations in edible tissues of pigs, whereas feces and urine were satisfactory for predicting SAL concentrations in edible tissues of goats. These data make it is possible to pre-slaughter monitoring SAL residues in edible tissues of pigs and goats.